Ethnicity, Obesity, and Type 2 Diabetes of Adults in Urban Populations of Central America - William G Wuenstel; James A. Johnson; James Humphries; Cheryl Samuel (International Journal of Public Health Science (IJPHS), 2017)
The purpose of this meta-analysis was to examine the impact of ethnicity and obesity as it relates to Type-2 Diabetes (T2D) in specific Central American countries. A meta-analysis was conducted to determine the association of ethnicity, obesity, and T2D.  Four studies that qualified for inclusion were identified by searching MEDLINE and PubMed databases. The studies on the association of ethnicity and T2D had a combined population resulted in 265,858 study participants.  Two studies on the association of obesity and T2D had 197,899 participants. An analysis of the data was conducted utilizing the relative risk ration, odds ratio, and forest plots. The comparison of the relative risk of T2D across ethnic categories by studies range for Blacks was 1.59 to 2.74, Asians was 1.43 to 2.08, and Hispanics .92 to 2.91. The ethnic difference in the prevalence of diabetes was almost two-fold higher in all ethnic groups than among the Caucasians with a significance level of 95%. A comparison of relative risk of T2D across weight categories was significantly higher among those with a diagnosed of diabetes in all reported areas. The odds ratio was very close to the risk ratio in both ethnicity and obesity to the development of T2D.The meta-analysis findings documented that an association does exist between ethnicity and obesity to the development of type 2 diabetes.